2021
DOI: 10.1021/acs.langmuir.1c01628
|View full text |Cite
|
Sign up to set email alerts
|

Sintering Rate and Mechanism of Supported Pt Nanoparticles by Multiscale Simulation

Abstract: Thermal stability is the key issue in the industrial application of supported metal nanocatalysts. A combination method of density functional theory calculations, machine learning, and molecular dynamics simulation is adopted to study the sintering behavior of supported platinum (Pt) nanoparticles on graphene or TiO 2 nanosheet, and analyze sintering mechanisms under different temperatures, particle sizes, and metal support interactions (MSIs). The results show that the agglomeration of supported nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This distance can effectively demonstrate the particle sintering behavior at different temperatures in the current system. 37 The time step is also 1 fs, simulating 500 ps under the NVT ensemble at 300 K. Subsequently, rapidly increase the temperature to the specified value (within 100 ps) just before the upcoming sintering process simulation. During the sintering stage, employ the NVE ensemble, and observe the sintering state of the particles.…”
Section: Interface Heat Transfer and Sintering Kinetics Simulationmentioning
confidence: 99%
“…This distance can effectively demonstrate the particle sintering behavior at different temperatures in the current system. 37 The time step is also 1 fs, simulating 500 ps under the NVT ensemble at 300 K. Subsequently, rapidly increase the temperature to the specified value (within 100 ps) just before the upcoming sintering process simulation. During the sintering stage, employ the NVE ensemble, and observe the sintering state of the particles.…”
Section: Interface Heat Transfer and Sintering Kinetics Simulationmentioning
confidence: 99%
“…Besides, several types of supports have been explored, among which oxide supports (Al 2 O 3 , SiO 2 , and TiO 2 and zeolites have been widely applied. Some catalysts with high catalytic activity often suffer from rapid deactivation and poor regeneration ability on account of coke accumulation and/or sintering of active compounds under the high temperature required in the reaction and regeneration processes. Coke deposition can occur on both the active compounds and th esupport surface, ultimately leading to catalytic deactivation by impeding mass transfer and poisoning the active sites. Sintering is a process where the supported active compounds agglomerate via a particle migration and coalescence process or the Ostwald ripening process into bigger particles. , Coke formation, coupled with the sintering behavior, is usually inevitable, resulting in an inexorable catalytic deactivation.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] In addition, dissolution processes during catalytic reactions and due to interactions with the electrolyte can lead to material loss. [11,[14][15][16][17] Recent studies have shown that while TM NPs bind weakly to pristine graphene, defect sites in graphene can serve as anchor points that greatly increase binding strength. Interestingly, this anchoring effect is prominent in particular for small TM clusters, which can fit into defects that are only several atoms wide where they covalently bind to the unsaturated carbon atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11–13 ] In addition, dissolution processes during catalytic reactions and due to interactions with the electrolyte can lead to material loss. [ 11,14–17 ]…”
Section: Introductionmentioning
confidence: 99%